Non-tuberculous mycobacterial lung disease in patients with bronchiectasis: perceived risk, severity and guideline adherence in a European physician survey - Dirk Wagner; Jakko van Ingen; Roald van der Laan; Marko Obradovic (BMJ Open Respiratory Research)
Background Patients with bronchiectasis are at increased risk of developing non-tuberculous mycobacteria lung disease (NTM-LD), and published guidelines recommend regular testing for NTM infection in this patient population.Objective This study aimed to survey physicians managing patients with bronchiectasis to understand the perceived risk of NTM to their patients, perceived disease severity and frequency of testing for NTM.Methods The study comprised an online survey of hospital-based physicians in the UK, Germany, Italy, France and the Netherlands. The target group were hospital-based physicians who had managed at least 10 adult patients with bronchiectasis over the preceding 12 months.Results In total, 280 physicians completed the survey. Most (87%) thought their patients to be at particular risk of NTM, although it was perceived as a moderate risk versus other respiratory pathogens. Most perceived NTM-LD to impact patient morbidity (84%), and 61% indicated that NTM-LD significantly impacted mortality. 68% of all respondents did not test for NTM prior to initiating macrolide monotherapy, despite guidelines recommending testing. The perceived risk of and screening for NTM varied among countries.Conclusions The study demonstrates that physicians understand the risk of NTM-LD and associated morbidity in patients with bronchiectasis; however, a minority do not perceive that NTM-LD significantly affects mortality. Greater awareness of the need to test for NTM infection before initiating macrolide monotherapy for bronchiectasis is essential due to potential emergence of drug-resistant NTM.